Behavioral state-dependent oscillatory activity in prefrontal cortex induced by chronic social defeat stress - Liu, Tiaotiao; Qi, Chengxi; Bai, Wenwen; Tian, Xin; Zheng, Xuyuan (Frontiers in Neuroscience, 2022)
Chronic stress contributes to the onset and exacerbation of major depressive disorder (MDD) through the oscillatory activity in prefrontal cortex (PFC). However, the oscillations on which chronic social stress converge to yield the behavioral state of social avoidance are largely unknown. Here we use a chronic social defeat stress model and in vivo electrophysiological recordings to uncover a novel neurophysiological measure that predicts social behavioral state in stressed animals. Firstly, we identify that chronic social defeat stress model induces depression-like behaviors (anhedonia, and social avoidance). Secondly, we find statistically significant differences in PFC oscillatory activity across different frequency ranges in social behavioral state and the oscillatory activity correlates with stress-induced behavioral state. Finally, we show that the social behavioral states are accurately decoded from the oscillatory activity based on machine learning. Together, these results demonstrate that naturally occurring difference in PFC oscillation underlie social behavioral state that accompany the emergence of stress-induced behavioral dysfunction.